2019
DOI: 10.22161/ijeab.46.44
|View full text |Cite
|
Sign up to set email alerts
|

Pig Droppings: A Potential Biostimulatory Candidate for Bioremediation of Diesel Oil-Polluted Soil

Abstract: The effectiveness of pig droppings (PD) in enhancing bioremediation of diesel oil-polluted soil was investigated gravimetrically for a period of 42 days. Polluted soil was amended with 5%, 10% and 15% (w/w) of PD. Loss of total petroleum hydrocarbon (TPH), microbial growth and germination indices were all monitored throughout the study period. At the end of 42 days, there was significant oil loss of 48.54% in the amended soil. Hydrocarbonutilising bacterial (HUB) counts were higher in the amended option rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The results from our study showed significant reduction in the level of used motor oil contamination in the potato skin-amended soil In the present study, potato skin had higher nitrogen content than the experimental soil (Table 1). Nitrogen and phosphorus have been reported as essential nutrients for bioremediation of petroleum hydrocarbons in the soil [19]. In other words, as bioremediation progresses in the absence of external nutrient sources such as nitrogen, carbon, phosphorus etc., the microorganisms will utilize available nutrients in the soil to a point of depletion and the nutrients becomes limiting.…”
Section: Discussionmentioning
confidence: 99%
“…The results from our study showed significant reduction in the level of used motor oil contamination in the potato skin-amended soil In the present study, potato skin had higher nitrogen content than the experimental soil (Table 1). Nitrogen and phosphorus have been reported as essential nutrients for bioremediation of petroleum hydrocarbons in the soil [19]. In other words, as bioremediation progresses in the absence of external nutrient sources such as nitrogen, carbon, phosphorus etc., the microorganisms will utilize available nutrients in the soil to a point of depletion and the nutrients becomes limiting.…”
Section: Discussionmentioning
confidence: 99%